The Number and the Size Distribution of Firms in Sweden and Other European Countries - Dan Johansson (The Research Institute of Industrial Economics (IUI), 1997)
This study investigates changes in the number and the size distribution of firms in Sweden in the period 1968-1993. The number and the size distribution of Swedish firms are compared to the number and the size distribution of firms in eleven European countries. A decrease in the number of enterprises in the Swedish manufacturing industry is observed in all size classes and intermediate-sized (10-199 employees/firm) firms declined the most. Large differences are found in the number of firms between countries. Data indicate that Sweden has fewer small (10-99 employees/firm) and more large-sized (500+ employees/firm) firms than other European countries. However, we find no support for the standard claim that Sweden has fewer medium-sized (100-499 employees/firm) firms than other European countries.
Keywords: F23; L11; 330; Industry Structure; Size Distribution of Firms; Betriebsgrößenstruktur; Schweden; EU-Staaten